2009
DOI: 10.1159/000228079
|View full text |Cite
|
Sign up to set email alerts
|

Y-Box Protein 1 Stimulates Mesangial Cell Proliferation via Activation of ERK1/2

Abstract: Aims: To investigate the effects of Y-box protein 1 (YB-1) on the mitogen-activated protein kinase pathway to ascertain which signaling pathway is involved in YB-1-induced mesangial cell (MC) proliferation. Methods: The rat MC line HBZY-1 was transfected with pcDNA3.1-YB-1. Cell proliferation was determined by [3H]thymidine incorporation, cell counting and cell-cycle analysis. The expression of cyclins was examined by real-time RT-PCR and immunoblotting analysis. Phosphorylation of c-Raf, MEK1/2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Therefore, the present study may have revealed the undiscovered function of YB-1 as a proteasomal regulator. The specificity between YB-1 and ERK2, and YB-1 and Raf-1 can be supported by the previous findings that ERK2 phosphorylated YB-1 (11) and Raf-1 regulation by YB-1 (38). Furthermore, considering the distinct role of Raf and ERK isoforms, the selective binding of YB-1 to Raf-1 and ERK2, but not to A-Raf, B-Raf and ERK1, makes us curious on this specificity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, the present study may have revealed the undiscovered function of YB-1 as a proteasomal regulator. The specificity between YB-1 and ERK2, and YB-1 and Raf-1 can be supported by the previous findings that ERK2 phosphorylated YB-1 (11) and Raf-1 regulation by YB-1 (38). Furthermore, considering the distinct role of Raf and ERK isoforms, the selective binding of YB-1 to Raf-1 and ERK2, but not to A-Raf, B-Raf and ERK1, makes us curious on this specificity.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, Lee and colleagues indicated that YB-1 knockdown decreased STAT3 phosphorylation at Ser727 in breast cancer, accompanied by decreases of ERK and mTOR phosphorylation (16), although a mechanical investigation was not conducted. Furthermore, Feng and colleagues reported that YB-1 induced rat mesangial cell proliferation through ERK1/2 signaling, and ERK regulated YB-1 expression under inflammatory conditions (38). For the first time, the present study elucidated the mechanism of MEK/ERK/RSK regulation by YB-1.…”
Section: Discussionmentioning
confidence: 49%
“…It was found that an elevated YB-1 amount correlates with expression of proliferation markers [33], YB-1 overexpression causes hyperplasia [34], and cell doubling time increases with decreasing YB-1 expression under the action of siRNAs [35]. But the opposite may be speculated too, i.e., that YB-1 synthesis decreases as a result of a slower cell division.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence indicates that abnormal growth of glomerular mesangial cells is an early event in various glomerular diseases and is the main histopathological feature in chronic kidney diseases (CKD) [1, 2]. Various signaling molecules are involved in mesangial cell proliferation and ECM accumulation [3-5].…”
Section: Introductionmentioning
confidence: 99%